Urgensi Pengembangan Prinsip Fiqh Toleransi dalam Pluralitas Negara Indonesia Pada Cyberspace - Apriliah; Siti; Riska; Muhammad Ubaidillah (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This paper examines the urgency of developing the principle of Islamic jurisprudence (fiqh) of tolerance within the plurality of Indonesian cyberspace. Using qualitative methods through library research and literature reviews from previous research, this paper concludes that: in cyberspace, we encounter various differences arising from differences of opinion, belief, and so forth. Therefore, it is crucial to instill the principle of Islamic jurisprudence (fiqh) of tolerance within a pluralistic society. Seeing how many people today are following technological developments, this naturally leads everyone to join social media, which transcends time, scope, and age. Currently, almost everyone conducts their activities on social media, and social media has even become a primary need for some. It's undeniable that this can lead to a variety of content being discovered. Thus, there are several principles of Islamic jurisprudence (fiqh) tolerance that must be instilled in everyone, including: first, accepting differences in belief (every social media user in cyberspace certainly has their own beliefs). Second, mutual respect for others' choices. Third, the right to freedom of expression (this is certainly very important because everyone has their own perspectives and thoughts). What must be ingrained in a person is not to feel right and force others to follow their own words or views.